Medicaid managed care and preventable emergency department visits in the United States - Toseef, Mohammad Usama (PLoS One, 2020)
OBJECTIVES: In the United States the percentage of Medicaid enrollees in some form of Medicaid managed care has increased more than seven-fold since 1990, e.g., up from 11% in 1991 to 82% in 2017. Yet little is known about whether and how this major change in Medicaid insurance affects how recipients use hospital emergency rooms. This study compares the performance of Medicaid health maintenance organizations (HMOs) and fee-for-service (FFS) Medicaid regarding the occurrence of potentially preventable emergency department (ED) use. METHODS: Using data from the 2003–2015 Medical Expenditure Panel Survey (MEPS), a nationally representative survey of the non-institutionalized US population, we estimated multivariable logistic regression models to examine the relationship between Medicaid HMO status and potentially preventable ED use. To accommodate the composition of the Medicaid population, we conducted separate repeated cross-sectional analyses for recipients insured through both Medicaid and Medicare (dual eligibles) and for those insured through Medicaid only (non-duals). We explicitly addressed the possibility of selection bias into HMOs in our models using propensity score weighting. RESULTS: We found that the type of Medicaid held by a recipient, i.e., whether an HMO or FFS coverage, was unrelated to the probability that an ED visit was potentially preventable. This finding emerged both among dual eligibles and among non-duals, and it occurred irrespective of the adopted analytical strategy. CONCLUSIONS: Within the U.S. Medicaid program, Medicaid HMO and FFS enrollees are indistinguishable in terms of the occurrence of potentially preventable ED use. Policymakers should consider this finding when evaluating the pros and cons of adopting Medicaid managed care.